2022
DOI: 10.3390/foods11101424
|View full text |Cite
|
Sign up to set email alerts
|

Commercial Baby Foods Aimed at Children up to 36 Months: Are They a Matter of Concern?

Abstract: Proper nutrition in infancy and early childhood is crucial to ensuring optimal child development, growth, and better health outcomes later in life. The nutrient profile model proposed by WHO/Europe aims to assess the nutritional quality and promotional/marketing aspects of commercial baby foods aimed at children up to 36 months. We used commercial data from 191 baby foods collected between March 2021 and July 2021, from eight supermarket chains in the Lisbon Metropolitan area. According to the model specificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
0
8
1
Order By: Relevance
“…Overall, the nutritional quality of baby biscuits in this study was very similar to recent findings from Grammatikaki et al (2021) on 233 baby biscuits and rusks from 27 European countries. In contrast, all baby biscuits in our study contained added free sugar, while other studies (e.g., Grammatikaki et al, 2021;Hutchinson et al, 2021;Santos et al, 2022) found a percentage of products with no added free sugar. Also, some studies have described lower values of salt as compared to the present study (Elliott, 2011;Elliott & Conlon, 2014;Garcia et al, 2020;McCann et al, 2022).…”
Section: Nutritional Quality Evaluation Of Biscuitscontrasting
confidence: 99%
“…Overall, the nutritional quality of baby biscuits in this study was very similar to recent findings from Grammatikaki et al (2021) on 233 baby biscuits and rusks from 27 European countries. In contrast, all baby biscuits in our study contained added free sugar, while other studies (e.g., Grammatikaki et al, 2021;Hutchinson et al, 2021;Santos et al, 2022) found a percentage of products with no added free sugar. Also, some studies have described lower values of salt as compared to the present study (Elliott, 2011;Elliott & Conlon, 2014;Garcia et al, 2020;McCann et al, 2022).…”
Section: Nutritional Quality Evaluation Of Biscuitscontrasting
confidence: 99%
“…Product labels also revealed concerning practices, with nearly all labels displaying an inappropriate claim. The high prevalence of claims on CPCF finger foods/snacks has been noted previously among products available in HIC contexts Santos et al, 2022), with some research showing an increase in the number of claims on CPCF labels .…”
Section: Discussionmentioning
confidence: 78%
“…According to Santiago (2022), the values of reducing sugars found show the presence of glucose in the composition of baby food, and the levels of non-reducing sugars indicate the presence of sucrose in these foods. Santos et al (2022) in a study of label analysis of infant foods, found that the majority had irregularities that compromised child health and were in non-compliance with the recommendations of the World Health Organization for nutritional labeling.…”
Section: Discussionmentioning
confidence: 99%